Asuhan Keperawatan pada Lanjut Usia Dengan Masalah Keperawatan Defisit Pengetahuan pada Diagnosa Medis Gout Arthritis - Syamsidar, Syamsidar; Darmiati, Darmiati; Yaman, Imran; Prana Anggara, Lestari (Yayasan Mandar Indonesia, 2023)
Uric acid is an additional result of normal metabolism and digestion of protein and foods that cortain purine (especially offal and several types of vegetables such as nuts and beans). This study aims to determinan the description of nursing care for erderly people with knowledge deficit nursing problems in the medical diagnosis of gout arthritis in the Wonomulyo community health center working area. This research method uses a descriptive method with a case study approach on one erderly person who meets the inclusion creteria, who is in the Wonomulyo community health center working area. Data colletion in this research included observation interviews and physical examinations and sace studies. The results of the research conducted by this researcher showed that of the 4 respondents, 3 respondents had sufficient knowledge and a good attitude, while 1 respondent had insufficient knowledge and a good attitude. For health, especially nurses, in providing nursing care for erderly people who experience gout arthritis with knowledge deficit problems, more emphasis is placed on the aspect of providing more accuarate information.